Risk Assessment of Gram-Negative Sepsis in Cardiac Surgery: From Clinical and Anamnestic Predictors to a Prognostic Model - Kostiantyn P. Chyzh; Hanna B. Koltunova; Andriy.P. Mazur; Mikhailo Yu. Antomonov; Nataliia M. Verych (Ukrainian Journal of Cardiovascular Surgery, 2025)
Gram-negative sepsis remains a serious threat to cardiac surgery patients. The incidence of gram-negative sepsis at the preoperative stage accounts for 10-25 % of all reported cases. In the postoperative period, gram-negative bacteria were responsible for sternal wound infections in 35 % of cases and caused bacteremia in 11 % of cases. Preoperative assessment of the risk of gram-negative sepsis represents an essential component of the clinical strategy in cardiac surgery.Aim. To investigate the clinical, laboratory, and anamnestic risk factors associated with the development of gram-negative sepsis in cardiac surgery patients, with the goal of constructing a prognostic model to identify high-risk patients at the preoperative stage.Materials and methods. The study included clinical data from 116 patients who underwent examination and treatment at the M.M. Amosov National Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine between January 1, 2020, and January 1, 2025. Inclusion criteria were bacteriological identification of a gram-negative pathogen in blood cultures at any stage of treatment, admission to the intensive care unit (ICU), and age over 18 years.Results. Multivariate analysis showed that identification of a gram-negative pathogen in a chronic wound at the preoperative stage was most strongly associated with an increased likelihood of sepsis development (OR=18,101.36; 95 % CI: 13.95-23,487,640.00; p<0.05). The presence of more than two intravenous catheters in the ICU significantly increased the risk of gram-negative sepsis (OR=376.86; 95 % CI: 4.15-34,210.14; p<0.05). Use of corticosteroids in the ICU prior to the diagnosis of sepsis increased the odds of developing gram-negative sepsis by 7.55 times (95 % CI: 1.31-43.35; p<0.05). To assess the prognostic performance of the developed multivariate model, a ROC curve was constructed, demonstrating an AUC of 0.96, with a sensitivity of 90 % and a specificity of 90 %.Conclusions. The study demonstrated that the key independent risk factors for the development of gram-negative sepsis were preoperative colonization of a chronic wound with gram-negative flora, a high frequency of intravascular device use in the ICU, and the immunosuppressive effect of corticosteroid therapy.